Toponymy of Garden Names at Lahu Village - James Edward Lalira (Phonologie : Journal of Language and Literature, 2022)
Abstract. This study aims to analyze the lingual form and to describe the phenomenon of naming place in Lahu village, Talaud regency, North Sulawesi Province with Talaud language as the object. Naming places refers to ethno linguistics study, a study that examining language and history. When it is formed, where it comes from, and what the reasons for naming it often become the main topics in research. For the purpose of analysis, the researcher examines the lingual form and the process of word formation. After that, the writer describes the determinant factors of naming places. This is a qualitative study with descriptive approach. In collecting data, the researcher uses listening and speaking method from Mahsun (2005). The listening method is used to collect data in the lingual form and phenomenon of naming place which appear in a speech. The Padan and Distribution are the method used to analysis data. These method process two data analyzing techniques, namely (1) Intralingual and (2) Technique of analyzing the smallest element. According to the research result, stem dominates the naming of places beside caused by affixation, reduplication and composition. For example: Niure [niure] ‘took back, Soa [soa] ‘vilage, Tatarangan [tataraµan] ‘track’, Linturran [incline] ‘turunan’, Ritawu [ritawu] ‘lose track’, Wawombatu, [wawombatu] ‘rock hill’, Panentean [panentean] ‘hillside, Nato [nato] ‘wood Nyato or Nato. Name of the land with the above lingual form is identity of the location. It is an inseparable part of a process. It is believed that naming a place is part of ancestral experience that has attempted to mark and to give identity on every known land location. In terms of naming place domination, the writer finds seven dominations. They are soil structure, plants, lake, process of morphologies, history, adjective, and object. Kata kunci: Toponymy, Talaud Language, Lahu